The Full-Service Community School Movement - Richardson, J. author. aut Link
VIII, 189 p.
Keywords: This book contributes in multiple dimensions to the educational literature through an articulation of T.J. and Anita Anderson's vision; how the community and faculty adopted the vision; what it meant in practical terms to matriculating students and their families; and, espouses lessons applicable in the 21st Century.